A Comparative Study on Chemical Compositions and Biological Activities of Four Amazonian Ecuador Essential Oils: Curcuma longa L. (Zingiberaceae), Cymbopogon citratus (DC.) Stapf, (Poaceae), Ocimum campechianum Mill. (Lamiaceae), and Zingiber officinale Roscoe (Zingiberaceae) - Alessandra Guerrini; Massimo Tacchini; Ilaria Chiocchio; Alessandro Grandini; Matteo Radice; Immacolata Maresca; Guglielmo Paganetto; Gianni Sacchetti (MDPI AG, 2023)
Essential oils (EOs) and their vapour phase of Curcuma longa (Zingiberaceae), Cymbopogon citratus (Poaceae), Ocimum campechianum (Lamiaceae), and Zingiber officinale (Zingiberaceae) of cultivated plants grown in an Amazonian Ecuador area were chemically characterised by Gas Chromatography-Flame Ionization Detector (GC-FID), Gas Chromatography-Mass Spectrometry (GC-MS), and Head Space-Gas Chromatograph-Flame Ionization Detector-Mass Spectrometry (HS-GC-FID-MS).figure The EOs analyses led to the identification of 25 compounds for C. longa (99.46% of the total; ar-turmerone: 23.35%), 18 compounds for C. citratus (99.59% of the total; geraniol: 39.43%), 19 compounds for O. campechianum (96.24% of the total; eugenol: 50.97%), and 28 for Z. officinale (98.04% of the total; α-Zingiberene: 15.45%). The Head Space fractions (HS) revealed C. longa mainly characterised by limonene and 1,8-cineole (37.35%) and α-phellandrene (32.33%); Z. officinale and C. citratus showed camphene (50.39%) and cis-Isocitral (15.27%) as the most abundant compounds, respectively. O. campechianum EO revealed a higher amount of sesquiterpenes (10.08%), mainly characterised by E-caryophyllene (4.95%), but monoterpene fraction remained the most abundant (89.94%). The EOs were tested for antioxidant, antimicrobial, and mutagen-protective properties and compared to the Thymus vulgaris EO as a positive reference. O. campechianum EO was the most effective in all the bioactivities checked. Similar results emerged from assaying the bioactivity of the vapour phase of O. campechianum EO. The antioxidant and antimicrobial activity evaluation of O. campechianum EO were repeated through HP-TLC bioautography assay, pointing out eugenol as the lead compound for bioactivity. The mutagen-protective evaluation checked through Ames's test properly modified evidenced a better capacity of O. campechianum EO compared with the other EOs, reducing the induced mutagenicity at 0.1 mg/plate. However, even with differences in efficacy, the overall results suggest important perspectives for the functional use of the four studied EOs.